What is the relationship between body mass index and eating disorder symptomatology in professional female fashion models?. (November 2020) - Ralph-Nearman, Christina; Yeh, Hung-wen; Khalsa, Sahib S.; Feusner, Jamie D.; Filik, Ruth
Highlights: Higher BMI is associated with worse eating disorder symptoms in models and nonmodels. Most models and nonmodels with clinically significant eating disorder symptoms had normal BMIs. Using a <18.5 BMI cutoff is likely to miss female models with eating disorders. Abstract: Low body mass index (BMI<18/18.5) is utilized as a mandated cutoff for professional fashion model employment, based on assumptions that low BMI indicates eating disorder pathology. No previous studies have examined the association between experimenter-measured BMI and eating disorder symptomatology in professional fashion models. We measured BMI and Eating Disorder Examination Questionnaire (EDE-Q) responses in United Kingdom (UK) professional fashion models, and nonmodels. Characteristics were compared using robust standardized mean difference (rSMD) obtained via probability of superiority. Associations between BMI and eating disorder symptomatology were examined using robust regression, controlling for age. Models exhibited lower BMI but higher fat-percentage and muscle mass. On the EDE-Q, models had higher Restraint, Global, Eating, and Weight Concerns, and similar Shape Concern scores compared to nonmodels. BMI was positively associated with eating disorder symptoms in both groups, and all but one of the eight models with clinically significant EDE-Q level had ≥18.5 measured BMI. Lower BMI was not indicative of worse eating disorder symptomatology in models or nonmodels. Thus, using a low BMI cutoff (<18.5) may not be an appropriate single index of health for detecting elevated eating disorder symptoms in models. Different policies to protect models' health should be considered.